Supply chain risk management - Chiang, Kai Jun (Nanyang Technological University, 2021)
In the pursuit of cost efficiency, global supply chains have continued to prioritise short-term gains tailored for stable environments. This often leave them vulnerable to disruptions, which despite their low probability, carry high impact to the supply chains involved. The project thus investigates the sources of such disruptions, the potential risks they bring to supply chain, and risk management strategies to cope with this inevitable risk. The project will specifically explore the effectiveness of the risk mitigation strategies adopted by Procter and Gamble Philippines in response to the COVID-19 global pandemic. A case study on the company’s supply chain structure during the pandemic is conducted to gain insights into the mitigation strategies Procter and Gamble Philippines had implemented. To further validate the effectiveness of their redesign of their supply chain structure, a simulation model is created to compare the performance of the supply chain before and after the pandemic and redesign, in term of lead times, number of backorders and time to fulfil backorders. The results obtained are then used to help suggest effective mitigation strategies to develop more resilient supply chains against disruptions.